‘People tell me quite intimate things’: The circulation of feelings and vague intimacy on politicised Instagram - Lehto Mari; Mannevuo Mona (Sage Journals, 2023)
In recent years, Instagram has become an increasingly politicised platform. Even those who have become popular for producing lifestyle content have begun to merge societal issues with personal and commercial posts. In this article, we explore how popular Finnish influencers experience the new expectations set for them and how they handle the mixture of intimate and algorithmic logics of Instagram. Our analysis draws from eight semi-structured, in-depth interviews with influencers and influencer agency representatives. Theoretically, we use the lexicon of cultural and media theory to examine Instagram as a platform for vague intimacy, where feelings and commercial exchange flourish and circulate in proximity to the political. The article revolves around three interconnected themes arising from the data: problems in producing political content for everyone, Instagram as a platform of likeness and the fear of an exploding inbox.